If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 = 9x + -2x Reorder the terms: 9 + 8x = 9x + -2x Combine like terms: 9x + -2x = 7x 9 + 8x = 7x Solving 9 + 8x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + 8x + -7x = 7x + -7x Combine like terms: 8x + -7x = 1x 9 + 1x = 7x + -7x Combine like terms: 7x + -7x = 0 9 + 1x = 0 Add '-9' to each side of the equation. 9 + -9 + 1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 0 + -9 1x = 0 + -9 Combine like terms: 0 + -9 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| -5*(3^2-2)+(7*5+7)/6 | | -x+1.9=0.4+2x | | y=cx-dx | | x-0.8=8.39 | | 6=8x+10 | | 35+8x= | | 32t=-160 | | (x+8)/10=8/5+(x-2)/3 | | r-4r-3s+10s-3t+8t=0 | | 4-1/3a=10 | | 6(m-6)+4(3m+4)=17(m-2)-2 | | 26+4y-10=13y-12-2y | | -13=k-16 | | 12x^2-25x-11=-4 | | 2x-4=2x+8/3 | | graphy+2=-2(x+4) | | 6y=28+2y | | 2x-3=12x | | 6(6m-2)= | | y/4+5=-16 | | 6(2x-1)-2(2x)=6 | | 3-2y+3= | | p^2+12p+40=8 | | x/5-6=0 | | 9-10x=161-38x | | 3x+35=12x-32 | | 8-(-10/3) | | 5x^2-21+22=0 | | 6x+68+12x=24 | | 5/9x+6/9=8/9 | | (x+8)(x+8)=-81 | | 5/6*-4 |